Les verbes de parole et la question de l’(in)transitivité - Béatrice Lamiroy; Michel Charolles (Discours)
The focus of the paper is the relationship between the syntax and the semantics of speech verbs. We hypothesize that speech verbs are naturally transitive because they refer to an activity which normally entails an object, viz. the produced speech. Most speech verbs are in effect transitive. However, to account for those verbs which are intransitive (e.g. bégayer, zozoter), we explore a second hypothesis based on a principle of semantic saturation: if the semantics of a verb is highly specific, then the verb is lexically saturated, and hence, syntactically intransitive. Verbs that indicate animal cries occupy a special position in that they are basically intransitive but lend themselves to transitive uses, especially in reported speech.